EVALUATION OF THE PERFORMANCE OF THE DOMESTIC WASTEWATER TREATMENT FACILITY OF A HOTEL IN PORT HARCOURT, RIVERS STATE NIGERIA (Nigerian Journal of Technology, 2016)
The efficiency of the biological treatment of domestic wastewater produced in a hotel in Port Harcourt, Rivers State, Nigeria sitting on a clay laden soil, was evaluated in this study. The biological treatment process involved is an activated sludge system. Wastewater from the hotel’s septic tank and treated water from the discharge from the activated sludge treatment plant was collected and analysis carried out in the laboratory to determine the extent of COD, BOD, TSS, NH3, Sulphate, TDS and Salinity in the wastewater as well as the treated water. The COD, BOD and TSS dropped from 45mg/l, 20.05mg/l and 35mg/l respectively to 20mg/l, 7mg/l and 10mg/l. While the NH3, Sulphate, TDS and Salinity dropped from 27.65mg/l, 450.08mg/l, 1800mg/l and 508.06 mg/l respectively to 11.55mg/l, 300mg/l, 1000mg/l and 450mg/l. The domestic wastewater treatment plant of 500m3/day capacity had an efficient treatment capability. All parameters, except, lead and chromium met DPR standard. However chromium met the FMENV Standard. The outlet wastewater after the treatment process also met the Federal Ministry of Environment Standard. The significance of the study is that the activated sludge wastewater treatment plant could be economically deployed in areas where there is availability of electricity and semi-skilled manpower..  http://dx.doi.org/10.4314/njt.v35i2.28